2020
DOI: 10.1021/acs.orglett.0c01110
|View full text |Cite
|
Sign up to set email alerts
|

Structural Revision of Lydiamycin A by Reinvestigation of the Stereochemistry

Abstract: Lydiamycin A (1) is a previously reported piperazic acid-bearing cyclic peptide from Streptomyces. The absolute configuration of lydiamycin A has not been fully determined despite the fact that multiple total syntheses have been reported. The absolute configuration of 1 was reinvestigated by the advanced Marfey’s method, chemical derivatization, and quantum-mechanics-based computational analysis, eventually resulting in a structural revision and establishment of the complete configuration. Lydiamycin A display… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 14 publications
0
16
1
1
Order By: Relevance
“…The position of C-2 was revised to S-configuration, instead of R as previously reported and C-19 and C-25 were assigned as S and R, respectively, which explained why none of four synthesized possible isomers based on the proposed structure with unassigned C-19 and C-25 displayed an NMR spectrum consistent with the natural compound. 18,20,21 Another route to piperazic acid employs Evans-type auxiliaries starting with bromide 18 (Fig. 6).…”
Section: Synthesis Of Free Piperazic Acidmentioning
confidence: 99%
“…The position of C-2 was revised to S-configuration, instead of R as previously reported and C-19 and C-25 were assigned as S and R, respectively, which explained why none of four synthesized possible isomers based on the proposed structure with unassigned C-19 and C-25 displayed an NMR spectrum consistent with the natural compound. 18,20,21 Another route to piperazic acid employs Evans-type auxiliaries starting with bromide 18 (Fig. 6).…”
Section: Synthesis Of Free Piperazic Acidmentioning
confidence: 99%
“…GG23 identified the production of lydiamycin A [15]. Detailed structure elucidation enabled us to revise the previously reported structure [16]. Analysis of the full genome of Streptomyces sp.…”
Section: Introductionmentioning
confidence: 97%
“…One of the first bioactive molecules obtained from symbiotic actinomycetes in insect ecosystems is dentigerumycin, a piperazic acid-bearing antifungal cyclic peptide isolated from a Pseudonocardia symbiont found on the exoskeleton of a fungus-growing ant ( Apterostigma dentigerum ) . Subsequent chemical investigations of insect-associated actinomycetes have revealed that a Streptomyces strain found in the gut of a mealworm ( Tenebrio molitor ) produces lydiamycin A, an antitubercular cyclic peptide, and the pentaminomycin family of autophagy-inducing cyclic peptides. , Actinobacterial communities associated with carrion beetles have also produced multiple nonproteinogenic amino acid-bearing NRPs, such as antibacterial nicrophorusamides including 5-chloro-tryptophan and β-hydroxyasparagine from Microbacterium sp. found in the gut of Nicrophorus concolor and antitubercular coprisamides containing β-methylaspartic acid and 2,3-diaminopropanoic acid isolated from Micromonospora sp.…”
Section: Introductionmentioning
confidence: 99%